Unveiling Interpersonal Depth: Social Penetration and Friendship Types in Nat Gould’s Fast as the Wind - Faulandi, Yussuf; Pawiro, Muhammad Ali; Ali, Nurbaiti; Efrizah, Doni (Universitas Islam Sumatera Utara, 2026)
Interpersonal relationships and friendship are central themes in literary works, yet they are rarely examined through communication theories such as Social Penetration Theory. This study addresses the limited application of communication theories in literary analysis by examining interpersonal relationships in Fast as the Wind by Nat Gould. It highlights the contribution of integrating communication theory into literary studies, particularly in understanding character interaction and relational development. A qualitative descriptive method is employed using content analysis of dialogues and narrative elements that reflect communication patterns and self-disclosure. The analysis reveals that social penetration occurs through four stages: orientation, exploratory affective exchange, affective exchange, and stable exchange, indicating a progression from superficial interaction to deeper emotional intimacy. Three types of friendship are identified: reciprocal, receptive, and associative, with reciprocal friendship as the most dominant. The results further show that trust, self-disclosure, and social context play significant roles in shaping interpersonal depth and relational dynamics among characters. The horse racing setting not only creates competition but also fosters cooperation and strong interpersonal bonds. These findings reinforce the relevance of communication theories in literary analysis and expand their applicability in interpreting interpersonal dynamics in fictional narratives.